1998
DOI: 10.2307/3004026
|View full text |Cite
|
Sign up to set email alerts
|

Population growth and air quality in California

Abstract: Demographers are often interested in the environmental impacts of population growth. I examine the impact of growth specifically on air quality in California. In recent decades, California has suffered from notoriously polluted air and has experienced rapid population growth. Despite the population growth, air quality actually has improved since the early 1980s due to aggressive regulatory efforts. Using data for 56 counties, I analyze the contribution of population growth to trends in atmospheric emissions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
1
13

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(92 citation statements)
references
References 10 publications
6
72
1
13
Order By: Relevance
“…Subsequent progress has been made, although much remains to be done. A good deal of this area's existing research focuses on the linkages between population dynamics and environmental change (e.g., Hunter, White, Little, & Sutton, 2003;Wust, Bolay, & Du, 2002;Nanu-Fabu, 2001;Bartlett, Mageean, & O'Connor, 2000;Cramer, 1998;Entwisle, Walsh, Rindfuss, & Chamratrithirong, 1998) or environmental context (e.g., Ness & Low, 2000;Hunter, 1998). Important contributions have also been made in understanding environmental degradation's human health consequences (e.g., Mishra, 2003).…”
Section: Background Literaturementioning
confidence: 99%
“…Subsequent progress has been made, although much remains to be done. A good deal of this area's existing research focuses on the linkages between population dynamics and environmental change (e.g., Hunter, White, Little, & Sutton, 2003;Wust, Bolay, & Du, 2002;Nanu-Fabu, 2001;Bartlett, Mageean, & O'Connor, 2000;Cramer, 1998;Entwisle, Walsh, Rindfuss, & Chamratrithirong, 1998) or environmental context (e.g., Ness & Low, 2000;Hunter, 1998). Important contributions have also been made in understanding environmental degradation's human health consequences (e.g., Mishra, 2003).…”
Section: Background Literaturementioning
confidence: 99%
“…On the other hand, the study conducted by Cramer (1998), based on a similar model, showed a contamination-population elasticity less than unity for the five pollutants analysed in several areas of the USA. This discrepancy could be explained by the exclusion of carbon dioxide among the pollutants considered by this author.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The first studies where based on cross-sectional data for only one time period. In this line, Cramer (1998Cramer ( , 2002 and Cramer and Cheney (2000) evaluated the effects of population growth on air pollution in California and found a positive relation only for some sources of emissions but not for others. Dietz and Rosa (1997) and York, Rosa and Dietz (2003) studied the impact of population on carbon dioxide emissions and energy use within the framework of the IPAT 1 model.…”
Section: Introductionmentioning
confidence: 99%
“…Cramer (134) in his study of California counties and Cole & Neumayer (136) in their cross-national studies found that other variables such as the percent of population that are migrants, age composition, household size, and level of urbanization have the same basic relationship as overall population size on emission levels of each of the pollutants they studied. However, caution should be used in interpreting these results because the studies only cover short time periods (10 to 20 years) in which there were only small changes in the demographic variables.…”
Section: Energy Air Pollution and Climate Changementioning
confidence: 99%
“…In quantifying the impacts of population on air pollution, researchers have reached different conclusions depending on which pollutants are under study, in which locations, at what scale, and for which time periods. For instance, a study of California counties shows that population size significantly contributes to the increase of the reactive organic gases NO x and CO and has little impact on PM 10 and SO x , which are derived more from production activities (134). Population size shows no significant relation to ground-level ozone because ozone is very difficult to measure at specific sites owing to its nature as a diffuse secondary pollutant (135).…”
Section: Energy Air Pollution and Climate Changementioning
confidence: 99%